Applied numerical methods with MATLAB for engineers and scientists - Chapra, Steven C. (Chennai, India : McGraw Hill Education, 2012)
Steven Chapra$1 (Bs Applied Numerical Methods with MATLAB, third edition, is written for engineering and science students who need to learn numerical problem solving. Theory is introduced to inform key concepts which are framed in applications and demonstrated using MATLAB. The book is designed for a one-semester or one-quarter course in numerical methods typically taken by undergraduates. The third edition features new chapters on Eigenvalues and Fourier Analysis and is accompanied by an extensive set of m-files and instructor materials.s
Mathematical modeling, numerical methods, and problem solving -- MATLAB fundamentals -- Programming with MATLAB -- Roundoff and truncation errors -- Roots : bracketing methods -- Roots : open methods -- Optimization -- Linear algebraic equations and matrices -- Gauss elimination -- Lu factorization -- Matrix inverse and condition -- Iterative methods -- Eigenvalues -- Linear regression -- General linear least-squares and nonlinear regression -- Fourier analysis -- Polynomial interpolation -- Splines and piecewise interpolation -- Numerical integration formulas -- Numerical integration of functions -- Numerical differentiation -- Initial-value problems -- Adaptive methods and stiff systems -- Boundary-value problems.
Includes bibliographical references and index.
Keywords: NUMERICAL ANALYSIS -- DATA PROCESSING -- TEXTBOOKS